Peran Inspektorat terhadap Pelaporan Harta Kekayaan Penyelenggara Negara di Setjen DPD RI - Fauziyah, Ade Zahro (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study aims to analyze the role of the Government Internal Supervisory Apparatus (APIP) in improving compliance with the reporting of State Officials’ Wealth Reports (LHKPN) within the Secretariat General of the Regional Representative Council of the Republic of Indonesia (Setjen DPD RI). Methodology/approach: Data were obtained through interviews and documentation studies. This study used interactive model data analysis techniques. Results/findings: Results/findings: Important findings regarding the implementation of the APIP role in improving compliance with LHKPN reporting, namely the APIP strategy, cross-unit collaboration, technical and cognitive barriers, the role of support staff, technical admin challenges, APIP communication innovation, and a compliance rate of 100%. Conclusions: APIP not only facilitates the reporting process but also plays a role in the initial verification, identification of reporting constraints, and provision of recommendations for follow-up actions on non-conformities. The achievement of a 100% compliance rate reflects the success of the strategy, both administratively and in increasing the awareness and ethical commitment of the state’s administrators. Strengthening APIP capacity, simplifying regulations, and increasing the intensity of education are priorities for maintaining the sustainability of an accountable and integrity-based reporting system. Limitations: This study is limited by its focus on a single institutional environment, which may not fully represent Indonesia’s broader public sector context. Contribution: These findings offer practical contributions to reinforce an integrity-based oversight culture and provide theoretical implications for the study of value management in the public sector.